2020
DOI: 10.1038/s41535-020-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous emergence of Josephson junctions in homogeneous rings of single-crystal Sr2RuO4

Abstract: The chiral p-wave order parameter in Sr2RuO4 would make it a special case amongst the unconventional superconductors. A consequence of this symmetry is the possible existence of superconducting domains of opposite chirality. At the boundary of such domains, the locally supressed condensate can produce an intrinsic Josephson junction. Here, we provide evidence of such junctions using mesoscopic rings, structured from Sr2RuO4 single crystals. Our order parameter simulations predict such rings to host stable doma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This indicates that the electrical transport properties of an SRO214 ring may depend on the ring geometry. To understand this, recently, Yasui et al [61] investigated SRO214 rings fabricated in two different geometries, as shown in Figure 3a,b. They observed SQUID-like oscillations in I c [58,59] at various different temperatures below T c , as shown in Figure 3c.…”
Section: Multiple Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the electrical transport properties of an SRO214 ring may depend on the ring geometry. To understand this, recently, Yasui et al [61] investigated SRO214 rings fabricated in two different geometries, as shown in Figure 3a,b. They observed SQUID-like oscillations in I c [58,59] at various different temperatures below T c , as shown in Figure 3c.…”
Section: Multiple Phasesmentioning
confidence: 99%
“…The colour maps show the Cooper-pair density |ψ| 2 .In the absence of a magnetic field, for a wider ring, the Meissner state is stable, and the chiral domain walls are stabilised by reducing the width of the ring wall. (Adopted with permission from[61] copyright NPG 2020).…”
mentioning
confidence: 99%
“…By using ultra-low currents (∽nA), we have confirmed that the insulating-state resistivity of the microscopic samples matches that of their mmsized counterparts, signaling the absence of strain. Moreover, in a previous work on the isostructural unconventional superconductor Sr 2 RuO 4 , we have prepared microscopic samples using equal methods and substrates 45 . These samples retained bulk properties to sizes below 200 nm, whereas, like Ca214, its transport properties are heavily dependent on strain [46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…The Little-Parks effect reflects the oscillation of the free energy of the superconductor as a function of the applied magnetic flux, resulting in a corresponding periodicity of the resistance near the superconducting transition temperature T c [79]. The minimum of the free energy [80,81], as well as the minimum of resistance, is achieved when the applied magnetic flux becomes (n + 1/2)Φ 0 for a superconducting loop containing an odd number of π-junctions [82][83][84][85], instead of nΦ 0 for a conventional s-wave superconducting loop. Here, n is an integer and Φ 0 = h/2e is the magnetic flux quantum with h Planck constant and e the elemental charge [86,87].…”
Section: Discussionmentioning
confidence: 99%